1999
DOI: 10.1023/a:1008312726163
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with fluorine-18-2-fluoro-2-deoxy-D-glucose (F18-FDG) does not visualize extranodal B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT)-type

Abstract: These discouraging results indicated that WB-FDG-PET is not useful for staging and follow-up of MALT-type lymphoma, and should therefore not be included in the clinical decision making process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(60 citation statements)
references
References 15 publications
5
53
0
2
Order By: Relevance
“…In 2 of their articles, Hoffmann et al reported poor tracer uptake in patients with MALT. 27,28 In contrast, Beal et al reported that MALT lymphoma could be detected with 18 F-FDG-PET in approximately 70% to 80% of patients and that there was no difference in detection between patients with lymph node and extranodal disease sites. 18 Our study, which, to our knowledge, includes the largest number of patients to date, supports the latter observation.…”
Section: Discussionmentioning
confidence: 97%
“…In 2 of their articles, Hoffmann et al reported poor tracer uptake in patients with MALT. 27,28 In contrast, Beal et al reported that MALT lymphoma could be detected with 18 F-FDG-PET in approximately 70% to 80% of patients and that there was no difference in detection between patients with lymph node and extranodal disease sites. 18 Our study, which, to our knowledge, includes the largest number of patients to date, supports the latter observation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies evaluating the sensitivity of FDG-PET in lymphomas showed conflicting results, particularly in indolent lymphomas. [5][6][7][8][9][10][11] We hypothesized that biologic differences between specific pathologic subtypes of lymphoma result in different degrees of FDG uptake and that utility of FDG-PET imaging varies between specific lymphomas. We retrospectively studied results of FDG-PET scans in patients with lymphoma using the World Health Organization (WHO) classification system to identify the specific subtypes reliably detected by FDG-PET.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas follicular lymphomas are FDG-avid in approximately 98% of cases, only 8/12 cases (67%) of (low-grade) marginal zone lymphoma were detected on PET in this series [73]. None of 10 cases of extranodal marginal zone lymphoma were detected by PET in another series [75]. Small lymphocytic lymphoma/chronic lymphocytic leukemia is also only variably FDG-avid, although a maximum standardized uptake value greater than 5 may raise suspicion for a large cell transformation [76].…”
Section: False Positives and Negativesmentioning
confidence: 53%